Shiitake mushroom powder supplementation increase antioxidative activity in dogs - Kusaba, Akio; Arai, Toshiro (Frontiers in Veterinary Science, 2024)
The prevalence of age-related diseases, including obesity (a lipid metabolism disorder), increases with the increase in a dog's lifespan. Most of age-related diseases are associated with oxidative stress by excessive production of reactive oxygen species (ROS) from impaired mitochondrial functions. Safe and effective supplements with antioxidative and anti-inflammatory activities are required to prevent obesity and associated complications. Shiitake mushroom exhibit various functions including antioxidant activity. We investigated the effect of shiitake powder supplementation in healthy dogs. Methods: Shiitake powder was supplemented at a dose of 800 mg/kg body weight /day for 4 weeks. The dose was set as 0.60-0.65 mg/kg/day of eritadenine, a hypocholesterolemic factor. Results: The body weight and body condition score of the dogs did not change after shiitake supplementation. In contrast, plasma total cholesterol concentrations decreased and superoxide dismutase activity and leukocyte sirtuin1 mRNA expression increased significantly in the dogs that received the supplement. Discussion: Oral administration of shiitake powder increased antioxidative activity. The supplement may be useful in ameliorating the signs of age-related diseases, including obesity, in dogs.